The complete mitochondrial genome of the hydrozoan jellyfish Spirocodon saltatrix (Cnidaria; Hydrozoa; Anthoathecata) with phylogeny analysis - Yoseph Seo; Jinho Chae; Jang-Seu Ki (Mitochondrial DNA. Part B. Resources, 2020)
In the present study, we sequenced and analyzed the complete mitochondrial genome of the hydrozoan jellyfish Spirocodon saltatrix. The mitochondrial genome was a linear form (15,752 bp long, 70.4% AT), consisting of 13 protein coding genes (cox1, cox2, atp8, atp6, cox3, nad2, nad5, nad6, nad3, nad4L, nad1, nad4, and cytB), two tRNAs (tRNA-Met and tRNA-Trp), and two rRNAs (12S and 16S). Mitochondrial gene arrangement of the S. saltatrix was completely identical to already-known mitochondrial genomes of hydrozoans. Molecular phylogenetic analysis using 13 protein-coding genes showed that S. saltatrix was closely related to the hydrozoan Clava multicornis.